Clinical behavior and outcomes of breast cancer in young women with germline BRCA pathogenic variants - Matteo Lambertini (Nature Portfolio, 2021)
Abstract Young breast cancer (BC) patients carrying a germline BRCA pathogenic variant (mBRCA) have similar outcomes as non-carriers. However, the impact of the type of gene (BRCA1 vs. BRCA2) and hormone receptor status (positive [HR+] vs. negative [HR−]) on clinical behavior and outcomes of mBRCA BC remains largely unknown. This is an international, multicenter, hospital-based, retrospective cohort study that included mBRCA patients diagnosed, between January 2000 and December 2012, with stage I–III invasive early BC at age ≤40 years. From 30 centers worldwide, 1236 young mBRCA BC patients were included. Among 808 and 428 patients with mBRCA1 or mBRCA2, 191 (23.6%) and 356 (83.2%) had HR+tumors, respectively (P < 0.001). Median follow-up was 7.9 years. Second primary BC (P = 0.009) and non-BC malignancies (P = 0.02) were more frequent among mBRCA1 patients while distant recurrences were less frequent (P = 0.02). Irrespective of hormone receptor status, mBRCA1 patients had worse disease-free survival (DFS; adjusted HR = 0.76, 95% CI = 0.60–0.96), with no difference in distant recurrence-free interval (DRFI) and overall survival (OS). Patients with HR+ disease had more frequent distant recurrences (P < 0.001) and less frequent second primary malignancies (BC: P = 0.005; non-BC: P = 0.18). No differences in DFS and OS were observed according to hormone receptor status, with a tendency for worse DRFI (adjusted HR = 1.39, 95% CI = 0.94–2.05) in patients with HR+ BC. Type of mBRCA gene and hormone receptor status strongly impact BC clinical behavior and outcomes in mBRCA young patients. These results provide important information for patients’ counseling on treatment, prevention, and surveillance strategies.